GERHANA; ANTARA MITOS, SAINS, DAN ISLAM - Sayful Mujab (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Moon eclipse and solar eclipse are two interesting natural phenomenon to be observed. Eclipses are among of the signs of Allah. It is him who put the sun and the moon in the orbit and moves with calculations that can be learned by humans. However, in addressing the eclipse events, there are differences among people. Some relates eclipse with various myths that grew up in their community. Some other believes that eclipse is a natural phenomenon that is closely related to science. There are also people interested in connecting eclipse with the viewpoint of Islam, that the event is a sign of the Oneness of Allah which can increase the quality of faith for those who want to take i’tibar or lesson from this event.Keywords: eclipse, myth, science, Islam.